Sexually transmitted infections related care-seeking behavior and associated factors among reproductive age women in East Africa: a multilevel analysis of demographic and health surveys - Ever Siyoum Shewarega; Elsa Awoke Fentie; Desale Bihonegn Asmamaw; Wubshet Debebe Negash; Samrawit Mihret Fetene; Rediet Eristu Teklu; Fantu Mamo Aragaw; Tewodros Getaneh Alemu; Habitu Birhan Eshetu; Daniel Gashaneh Belay (BMC, 2022)
Abstract Background Sexually transmitted infections are serious global public health issue, and their consequences contribute significantly to population morbidity and mortality, especially in Sub-Saharan Africa. However, there is limited information about the sexually transmitted infections related care-seeking behavior in East Africa. Therefore, this study aimed to assess the pooled prevalence of sexually transmitted infections related care-seeking behavior, and associated factors among reproductive-age women in East Africa using the recent Demographic and Health Survey. Methods This study was based on recent Demographic and Health Survey of 8 East African countries from 2008/09 to 2018/2019. A total weighted sample of 12,004 reproductive-age women who reported sexually transmitted infections or symptoms of sexually transmitted infections in the last 12 months wereincluded. A multi-level mixed-effect logistic regression model was used and a P-value of < 0.05 was considered a statistically significant level for identification of individual and community level factors and AOR with a 95% l CI was computed. Result The overall prevalence of sexually transmitted infections related care-seeking behavior among reproductive-age women in East African countries was 54.14% [95% CI: 53.25%, 55.03%]. In multilevel analysis: being age 25-34 [AOR = 1.27 95%CI: 1.15-1.41], 35-49 [AOR = 1.26 95%CI: 1.13-1.41], women who attained secondary or above education [AOR = 1.27, 95% CI: 1.09, 1.47], being in rich household [AOR = 1.27, 95% CI 1.14, 1.41], women who were currently pregnant [AOR = 1.29, 95% CI 1.13, 1.47], who had been tested for HIV [AOR = 1.99, 95% CI 1.70, 2.33], women who had one and more than one sexual partner [AOR = 1.18, 95% CI 1.05, 1.34], women who lived in urban area [AOR = 1.16, 95% CI: 1.03, 1.31] and who perceived distance from the health facility was not a big problem was [AOR = 1.13, 95% CI 1.04, 1.23] were significantly associated with sexually transmitted infections related care-seeking behavior. Conclusion sexually transmitted infections related care-seeking behavior is relatively low as compared with other studies.. This study revealed that individual-level variables such as women's age, educational status, household wealth index, pregnancy status, ever been tested for HIV, number of sexual partners, and community-level variables such as residence and distance from a health facility were associated with sexually transmitted infections related care-seeking behavior. Therefore, public health interventions targeting uneducated women, poor households, and adolescents, as well as improving counseling and awareness creation during HIV/AIDS testing and Antenatal care visits, are vital to improving sexually transmitted infections care seeking behavior.